User-oriented quality assessment of the Museu Capixaba do Negro: Application of the servqual theoretical-methodological approach in a museum space in Vitória-ES - Calderari Miguel, Marcelo; Fontenele Freire, Vitorino (Guará Journal, 2016)
This study evaluates the quality of services provided in Capixaba Museum Negro in the city of Vitoria/ES using the method Parasuraman, Zeithaml and Berry, the Servqual. Examines Importance matrix vs. Performance as a tool for data analysis in relation to the dimensions of quality: Reliability, Empathy, Warranty, Responsiveness and Tangibility. The methodology of this study has descriptive quantitative. Its kind is of survey type using questionnaire and critical incident technique. The results of this research evidence that customers consider Tangibility dimension that is important, and low it is rate of dissatisfaction. Another diagnosis demonstrates that users consider important and pleased the with the receptivity dimension. It is recommended to Servqual method for evaluating the quality of non-formal spaces of education and its use as a useful tool for management and decision-making, considering the strengths and weaknesses of the institutions presented in the search result, which generates information on the perspective of the customer.